Implications Of The Multibar Concept On Containers Advocates Organization (Peradi) Based On Decision Supreme Court No. 73/KMA/HK.01/IX/2015 - Fauziah Lubis; Rizki Winanti; Putri Nurhazijah; Rizka Putri Agustina S; Salma Salsabila; Salsabila Alamanda (Fox Justi : Jurnal Ilmu Hukum, 2025)
The purpose of this study is to determine the relationship between the issuance of Supreme Court Decision Number 73/KMA/HK.01/IX/2015 with the Multibar concept and to determine the negative impact of the Multibar concept if applied to the Advocate Organization in Indonesia. The problem in this study is because there has been a debate on the Supreme Court Decision Number 73/KMA/HK.01/IX/2015 which tends to favor the Multibar concept . This study uses the Normative Juridical method, namely analyzing problems through a legal principles approach that refers to legal norms contained in legislation. The results of the discussion, namely the issuance of the Supreme Court Decision Number 73/KMA/HK.01/IX/2015, show that if the decision is more in favor of the Multibar Concept, in this case it can certainly cause debate, chaos, violate higher laws, divide the Advocate Organization and can harm the Advocate profession.